Leopoldo Lugones against the gods: the prometean configuration of the gaucho’s arquetype in "El Payador" (1916) - Polotto Sabaté, María Lydia (Amaltea. Revista de Mitocrítica, 2012)
In this article we will demonstrate how Leopoldo Lugones builds up the archetype of the gaucho in his text El payador (1916) as a promethean character. In the first place, we will see that both Prometheus and the gaucho are taken as civilizing agents and that they accomplish their mission departing from a rebellious action against authority. Secondly, we will analyze why the punishment of these characters is important, so as to successfully achieve their civilizing mission.